“This is how real men do things you know.” Perpetrators perceptions of Intimate partner violence. - Turton, Natasha (My University, 2017)
Intimate Partner Violence (IPV) is a pervasive problem affecting many women in South Africa and worldwide. Due to the many consequences that victims of IPV experience, it is increasingly seen as a public health concern. Despite interventions targeted at reducing the rates of IPV, it still remains prevalent in South African communities. Research has mainly explored IPV from the victims’ perspective and only in recent years has there been a marked interest in perpetrators of IPV. This study explores an identified gap in literature which examines the experiences and actions of male perpetrators of IPV. In-depth interviews were conducted with five men who were a part of a perpetrator reintegration programme at a Non-Governmental Organisation in Johannesburg. The data was analysed using Interpretive Phenomenological Analysis in an attempt to better understand their reported individual experiences. The study found that there was little consensus amongst perpetrators of IPV regarding the nature and causes of violence. IPV is normalised by many perpetrators. It is embedded in a context of patriarchy which emphasizes male dominance over the household, the finances and the women and children. Men and women are socialized into the context of patriarchy. Through the research, it was found that perpetrators view their actions as a response to something their partner did wrong or did not do, thus the act is seen as justified, the use of blame and minimization of the act were common responses when asked about experiences of IPV. Traditional customs such as Lobola allowed men to believe that they owned their wives, and through this had dominance and control over the relationship. This was viewed by participants as a right to discipline and punish one’s partner.
A research project submitted in partial fulfilment of the requirements for the degree of Master of Arts (Psychology) in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, March 2017.
Keywords: Intimate partner violence--South Africa--Psychological aspects; Women--Violence against--South Africa; Masculinity--South Africa; Dating violence--South Africa